Answer:
The amount of 65 cents per pound flour to use is 40 pounds and the amount of 95 cents per pound flour to use is 60 pounds
Step-by-step explanation:
Let
x ----> amount of 65 cents per pound flour to use
y----> amount of 95 cents per pound flour to use
we know that
---->
----> equation A
----> equation B
substitute equation A in equation B
![0.65x+0.95(100-x)=0.83(100)](https://tex.z-dn.net/?f=0.65x%2B0.95%28100-x%29%3D0.83%28100%29)
Solve for x
![0.65x+95-0.95x=83](https://tex.z-dn.net/?f=0.65x%2B95-0.95x%3D83)
![0.95-0.65x=95-83](https://tex.z-dn.net/?f=0.95-0.65x%3D95-83)
![0.30x=12](https://tex.z-dn.net/?f=0.30x%3D12)
![x=40\ lb](https://tex.z-dn.net/?f=x%3D40%5C%20lb)
Find the value of y
![y=100-40=60\ lb](https://tex.z-dn.net/?f=y%3D100-40%3D60%5C%20lb)
therefore
The amount of 65 cents per pound flour to use is 40 pounds and the amount of 95 cents per pound flour to use is 60 pounds
Answer:
5
Step-by-step explanation:
4 7/12 + 5/12 = 4 12/12 which equals 5
Answer:
x= 60
Step-by-step explanation:
if y is the other missing side
y^2 = 64^2 + 48^2
y^2 = 4,096 + 2,304
y^2 = 6,400
100^2 = x^2 +y^2
x^2 = 10,000 - 6,400
x^2 = 3,600
x = 60
Step-by-step explanation:
17². + 144²=x²
289 + 20736=x²
x²=21025
x =√21025
x=145
145 miles apart
Answer:
5*2+1/2*-2
11/2*-2
-11
Step-by-step explanation: